Removal of copper (ii) ions from aqueous solutions by an isolated Fungal strain from mangrove soil environment in the Southeast Borneo - Wahab, A.A.; Ahmad, Husaini; Azham, Zulkharnain; Tay, Meng Guan; Hairul, Roslan (2014)
Heavy metal released into the environment is increasing continuously as an impact from industrialization and technological advancement. Industrial effluents containing heavy metals as well as the electronic wastes from various electrical and electronic industries contributed immensely to heavy metal pollution particularly Cu(II) ions. The use of biomaterials for removing heavy metals from contaminated soil and wastewater has emerged as a potential alternative method to the conventional techniques. The aim of this study is to isolate fungal strain capable of removing copper ions from aqueous solution. The study was able to isolate a fungal strain, identified as Penicillium citrinum UMAS B2 which showed an excellent potential for copper ion removal from aqueous solution. The uptake of Cu (II) ions was investigated and the biosorption experiments were carried out in batch mode. The experimental results showed that the maximum uptake of Cu (II) ions was obtained at pH 7 and temperature of 300 C. The maximum removal was obtained at 50mgL-1 of metal concentration with uptake of 5.566±0.960 mg/L. The observation in this study showed that the newly isolated Penicillium citrinum UMAS B2 can be used as a biosorbent for an efficient removal of Cu(II) ions from aqueous solution.